Archaik Beliefs of the Kyrgyz (based on the works of Ch. Aitmatov) - Мурзакметов, Абдымиталип (Scientific Journal of Faculty of Theology, 2018)
Ancient folk beliefs do not disappear with time, they continue to live in the depths of a person's soul. This article analyzes archaic beliefs of Kyrgyz people in the works of Chingiz Aitmatov.